A flauta improvisada por Léa Freire e Artur Andrés: um estudo sobre os contextos de atuação do improvisador e as ferramentas utilizadas para a improvisação - Alexandre Campos Amaral Viera Andrés (2022)
The universe of musical improvisation encompasses different procedures and tools to carry out creative music making in real time, treading the construction of melodic paths, as well as rhythmic and harmonic combinations in the act of performance, without the possibility of returning to the solution of possible edges. Freire and Andrés, both composers, flutists and improvisers, followed different paths within the scope of Brazilian Instrumental Music (MIB). Freire, inserted primarily in the tonal universe, produces music with a strong influence of Brazilian popular music, baião, frevo, choro, among other genres. Andrés, through nearly forty years of work with the Uakti Group and its new musical instruments, practices hybrid, tonalmodal improvisation, where the influence of Indian and minimalist music blends with Brazilian music and jazz. The analysis of transcriptions of improvisations by Freire and Andrés make it possible to raise questions related to the musical context in which they were inserted, as well as the musical grammars they developed, in their trajectory as idiomatic improvisers. Due to the fact that both are composers, it is also observed how improvisation can influence composition and, at the same time, how composition can influence the practice of improvisation.